COVID-19 Analysis in Tissue Samples Acquired by Minimally Invasive Autopsy in Out-of-Hospital Deaths with Postmortem Degeneration - Hirata, Yuichiro; Makino, Yohsuke; Iida, Shun; Katano, Harutaka; Nagasawa, Sayaka; Rokutan, Hirofumi; Hinata, Munetoshi; Iwasaki, Akiko; Yasunaga, Yoichi; Abe, Hiroyuki; Ikemura, Masako; Motomura, Ayumi; et al. (Japanese Journal of Infectious Diseases, 2023)
Minimally invasive autopsy (MIA) is an alternative to a full autopsy for the collection of tissue samples from patients’ bodies using instruments such as a biopsy needle. MIA has been conducted in many cases of coronavirus disease 2019 (COVID-19) and has contributed to the elucidation of the disease pathogenesis. However, most cases analyzed are hospital deaths, and there are few reports on the application of MIA in out-of-hospital deaths with varying extents of post-mortem changes. In this study, MIA and autopsies were performed in 15 patients with COVID-19 2–30 days after death, including 11 out-of-hospital deaths. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) genome detection by reverse transcriptase quantitative polymerase chain reaction using MIA samples was mostly consistent with autopsy samples, particularly lung tissue, even in out-of-hospital cases. MIA had high sensitivity and specificity (> 0.80). Histological examination of lung tissue obtained by MIA showed characteristics of COVID-19 pneumonia, with 91% agreement with autopsy samples, whereas localization of SARS-CoV-2 protein in lung tissue was indicated by immunohistochemistry, with 75% agreement. In conclusion, these results suggest that MIA is applicable to out-of-hospital deaths due to COVID-19 with various postmortem changes, especially when autopsies are not available.